전남지역 일부 치위생과 학생의 윤리교육에 따른 도덕성 발달수준 평가 - 김윤정; 임근옥; 유미선 (Han'guk Ch'iwisaeng Hakhoe chi, 2008)
This study was conducted to evaluated the level of moral development of dental hygiene students in Korea. Data were collected through self reported questionnaires received from 197 dental hygiene students from May 6 to 28, 2008. The Korean version of the DIT(Defining issues Test) was adopted to evaluate levels of moral development that the score of P(%) and stage 4. The data were analyzed by a descriptive analyses and t-test. The mean score of P(%) and stage 4 was 45.21±12.69 and 21.28±11.06 respectively. The score of P(%) revealed significant difference by experience of ethical education, medical ethics education and work ethics education and necessity of medical and work ethics education, clinical practice exercise. The score of stage 4 revealed significant differences by necessity of work ethics education, participation of ethics education and importance of ethics education. In conclusion, for enhancing dental hygienists' moral development it is necessary to improve the curriculum and to develop the ethics education This study was conducted to evaluated the level of moral development of dental hygiene students in Korea. Data were collected through self reported questionnaires received from 197 dental hygiene students from May 6 to 28, 2008. The Korean version of the DIT(Defining issues Test) was adopted to evaluate levels of moral development that the score of P(%) and stage 4. The data were analyzed by a descriptive analyses and t-test. The mean score of P(%) and stage 4 was 45.21±12.69 and 21.28±11.06 respectively. The score of P(%) revealed significant difference by experience of ethical education, medical ethics education and work ethics education and necessity of medical and work ethics education, clinical practice exercise. The score of stage 4 revealed significant differences by necessity of work ethics education, participation of ethics education and importance of ethics education. In conclusion, for enhancing dental hygienists' moral development it is necessary to improve the curriculum and to develop the ethics education KCI Citation Count: 5